The horrors of Auschwitz - Lombardo, Jennifer (World history (Lucent Press), 2017)
"Photographs, a detailed timeline, and excerpts from primary sources offer an in-depth look at the Nazis rise to power [and happenings at Auschwitz]"--Amazon.com.